Policy of Supply Chain Network in the Policy-Making Process: A Case of Communal Land Policy in Riau, Indonesia - Auradian Marta; Utang Suwaryo; Affan Sulaeman; Leo Agustino (International Journal of Supply Chain Management, 2020)
Abstract— Public policy and associated governmental regulatory issues play critical roles in shaping the practice of supply chain management. This study attempts to examine the role and concept of policy of supply chain network, particularly dialectical model proposed by Marsh Smith (2000) in explaining policy outcomes by taking a case study of communal land policy-making process. This study applies qualitative method and primary data collection techniques of in-depth interviews and document study. This study shows that dialectical model can be applied in explaining the role of policy network on the outcomes of communal land policy in Riau, Indonesia. The outcomes of communal land policy are determined by the dialectical relationship between structure and agency, network and context, network and outcome, as well as problem orientation from policy actors. Inside-government-actors dominate the policy-making process and create a limited network. Therefore, outside-government-actors do not have sufficient access to influence policy outcomes.